Living a One Planet Life: Experiences and Perceptions of the One Planet Development Policy - BENJAMIN TONGE (2023)
In 2010, the One Planet Development policy (OPD) was introduced as part of the Welsh Government’s wider vision to create a sustainable One Planet nation that only uses its fair share of resources. Specifically, OPD is a planning policy which allows people to build a home and create a land-based business in rural areas where developments are normally prohibited, provided that a strict set of ecologically orientated criteria are met, including having an ecological footprint as small as possible. To investigate how such OPD is being practised, semi-structured interviews and participant observation were utilised to explore areas that remain generally under-researched, such as the everyday lives, motivations, experiences and perceptions of those attempting to live One Planet Lives, whilst also placing these in the context of thoughts and issues raised by a range of otherstakeholders, such as planners, local councillors and the Welsh Government. OPD participants were found to be fully committed to living low impact lifestyles. They were motivated by political reasons and general concern for the environment but also by more personal reasons, such as wanting to be immersed in nature. Despite being happy in their lifestyle, the planning application stage and ongoing monitoring was seen as daunting and at times traumatic. It was also shown to be problematic and a burden for resource depleted local planning departments, serving to compound issues surrounding OPD. Indeed, tension has been generated by the different visions and meanings being projected onto the rural landscape, a key characteristic of the emerging post-productivist countryside and a sign of enduring crisis for rural space. Wales’s association with alternative living also permeated the study’s findings, along with wider issues shaping the current complexion of rural areas, such the pressure on conventional agriculture, general uncertainty for farmers and often an ongoing productivist mindset. These all fed into the debates surrounding OPD, curtailing its progress, frustrating meaningful understanding of OPD successes and limiting the possibility of applying lessons learned to other areas of policy. The study thus concludes by calling on the Welsh Government to review the policy to gain a first-hand understating of the issues and rework and re-emphasise the potential opportunities OPD offers.